El ensayo fotográfico como herramienta comunicacional de identidad cultural en el cantón El Guabo - Piedra Pacheco Cecilia Marlene (Machala, 2022)
The importance of strengthening cultural identity makes it possible to inquire about the culture and ethnicity to which a community belongs. Likewise, it is relevant to emphasize this research topic in order for people to learn more about their city or place of origin. Institutions should propose projects to strengthen historical photography, better known as heritage photography, which represents one of the most enriching sources of knowledge in culture; it makes it possible to deepen the understanding of the past, refresh the memory, evoke times, spaces, people, elements of society, historical processes and social changes in the Canton El Guabo Province of El Oro. For this reason, this work is aimed at promoting strategies and digital tools to promote cultural identity and, above all, to motivate young people to learn more about the canton of El Guabo, making photography an important role in the social and cultural sphere. For this reason, the following question is posed: How to elaborate a photographic essay that manages to strengthen the cultural identity of the canton of El Guabo? In this research, the following complementary problems were posed: What knowledge do young people have about the cultural identity of the canton of El Guabo? What are the characteristics of a photographic essay as a tool to strengthen the cultural identity of the canton of El Guabo? What is the impact of the photographic essay as a tool to strengthen the inhabitants of the canton of El Guabo? To answer these questions, a diagnosis of the object of study is applied and then an action plan is implemented, which includes a photobook of the canton of El Guabo. At the end of the study, the proposal is evaluated by the counterpart, highlighting their respective recommendations.
La importancia de fortalecer la identidad cultural permite indagar sobre la cultura y etnia a la que pertenece una comunidad. Así mismo, es relevante hacer énfasis en este tema de investigación para lograr que las personas conozcan más sobre su ciudad o lugar de origen. Las instituciones deben plantear proyectos para fortalecer la fotografía histórica, más conocida como fotografía patrimonial, representa en la cultura una de las más enriquecedoras fuentes de conocimiento; posibilita profundizar la comprensión del pasado, refresca la memoria, evoca tiempos, espacios, personas, elementos de la sociedad, procesos históricos y cambios sociales en el Cantón El Guabo Provincia de El Oro. Por esta razón, el presente trabajo va encaminado a impulsar estrategias y herramientas digitales que permitan fomentar la identidad cultural y, sobre todo, motivar a los jóvenes para que conozcan más acerca del cantón El Guabo, convirtiendo la fotografía en un papel importante en el ámbito social y cultural. Es por ello que se plantea la siguiente interrogante: ¿Cómo elaborar un ensayo fotográfico que logre fortalecer la identidad cultural del cantón El Guabo? En esta investigación se plantearon los siguientes problemas complementarios: ¿Cuáles son los conocimientos sobre la identidad cultural del cantón El Guabo que tienen los jóvenes? ¿Qué características tiene un ensayo fotográfico como herramienta para fortalecer la identidad cultural del cantón El Guabo? ¿Cuál es el impacto del ensayo fotográfico como herramienta de fortalecimiento en los habitantes del cantón El Guabo? Para responder estas interrogantes se aplica un diagnóstico del objeto de estudio y posteriormente se ejecuta un plan de acción que incluye un photobook del cantón El Guabo. Al finalizar el estudio, se evalúa la propuesta por la contraparte, destacando sus respectivas recomendaciones.
Keywords: FOTOGRAFIA; DOCUMENTAL FOTOGRAFICO; ARTE DOCUMENTAL; IMAGEN; CULTURA